Holocene sea ice variability driven by wind and polynya efficiency in the Ross Sea - K. Mezgec (Nature Portfolio, 2017)
Strong regional heterogeneity prevents thorough understanding of the recent increase in Antarctic sea ice. Here, analysis of marine and ice cores in the Western Ross Sea shows that late Holocene contrasting sea ice patterns between open and coastal areas are related to katabatic winds and polynya efficiency.